2004
DOI: 10.1056/nejmoa041869
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Survival in Follicular Lymphoma Based on Molecular Features of Tumor-Infiltrating Immune Cells

Abstract: The length of survival among patients with follicular lymphoma correlates with the molecular features of nonmalignant immune cells present in the tumor at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
978
5
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,280 publications
(1,034 citation statements)
references
References 29 publications
34
978
5
17
Order By: Relevance
“…Indeed, gene expression of, for example, IL7 receptor and STAT4 is part of the favorable immune response 1 signature of FL. 40 In our FL collective, the expression of pSTAT5 correlated with higher amounts of tumor-infiltrating regulatory T cells, which are also known to be associated with favorable outcomes. 25 Finally, we confirmed the prognostic importance of pSTAT3 in activated B-cell-like DLBCL, which was recently observed by others, 18 as our own nongerminal center DLBCL expressing pSTAT3 had also an inferior disease-specific survival, again indicating the oncogenic potential of pSTAT3.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, gene expression of, for example, IL7 receptor and STAT4 is part of the favorable immune response 1 signature of FL. 40 In our FL collective, the expression of pSTAT5 correlated with higher amounts of tumor-infiltrating regulatory T cells, which are also known to be associated with favorable outcomes. 25 Finally, we confirmed the prognostic importance of pSTAT3 in activated B-cell-like DLBCL, which was recently observed by others, 18 as our own nongerminal center DLBCL expressing pSTAT3 had also an inferior disease-specific survival, again indicating the oncogenic potential of pSTAT3.…”
Section: Discussionmentioning
confidence: 73%
“…39 Taking into account ROC-determined cutoff values of the respective markers, another noteworthy finding of our study was the identification of the favorable prognostic value of the concomitant pJAK2 and pSTAT5 expression in FL. One of the several possible explanations for this prognostic effect of the concomitant pJAK2 and pSTAT5 expression could be sought in the known ongoing immunological cross talk in a particular group of FL with better prognosis, 40 immunological cross talk being mediated by members of the STAT family at the intracellular site. Indeed, gene expression of, for example, IL7 receptor and STAT4 is part of the favorable immune response 1 signature of FL.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, extrinsic factors present within the tumor microenvironment likely contribute to the growth and survival of malignant T cells, a contention supported by the observation that cytokine supplementation or the provision of T-cell costimulatory signals supports the growth of malignant T cells in vitro [37,39,40]. Both gene-expression profiling and immunohistochemistry-based studies have recently highlighted the important contribution of nonmalignant cells, including monocyte-derived lymphoma-associated macrophages, in the pathogenesis of both Hodgkin and non-Hodgkin lymphomas [41][42][43]. Similarly, malignant T cells in the skin are frequently associated with dendritic cells and immunohistochemistry-based studies have clearly demonstrated an abundant infiltrate of both lymphoma-associated macrophages and dendritic cells, many of which may be actively recruited into the tumor microenvironment by tumor-derived chemokines [44,45].…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Gene expression profiling studies of various cancers have discovered consistent gene expression patterns associated with a histological or clinical phenotype and discovering subtypes of cancers previously unidentified with conventional technologies (Alizadeh et al, 2000;van de Vijver et al, 2002;Bullinger et al, 2004;Dave et al, 2004;Lapointe et al, 2004;Valk et al, 2004;Lee et al, 2004a;Roepman et al, 2005). This approach promises to provide diagnostic and prognostic markers that can be clinically used in the near future (Lossos et al, 2004).…”
Section: Integrative Functional Genomicsmentioning
confidence: 99%